1997
DOI: 10.1002/(sici)1097-0215(19970317)70:6<631::aid-ijc1>3.3.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

HLA class‐I‐restricted and tumor‐specific CTL in tumor‐infiltrating lymphocytes of patients with gastric cancer

Abstract: Immune recognition of human cancers except melanoma is not well understood at either the cellular or the molecular level. We demonstrate in this study the existence of HLA class-I-restricted and tumor-specific CTL in IL-2-activated TIL (tumor-infiltrating lymphocytes) of all 4 gastric cancer patients tested. We established HLA A2-restricted and adenocarcinoma-specific CTL in 2 HLA A0201 1 patients, and HLA A2402-restricted CTL recognizing both adenocarcinoma and squamous-cell carcinomas (SCC) in the 2 remainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Despite the expression of tumor rejection antigens such as melanoma antigens 1-3 [29] and the presence of tumor-specific cytotoxic T cells [30], the immune system fails to mount an effective immune response against gastric carcinoma cells, similar to findings in other cancers. However, the mechanisms by which gastric cancer cells overcome an antitumor immune response are poorly understood.…”
Section: Introductionmentioning
confidence: 69%
“…Despite the expression of tumor rejection antigens such as melanoma antigens 1-3 [29] and the presence of tumor-specific cytotoxic T cells [30], the immune system fails to mount an effective immune response against gastric carcinoma cells, similar to findings in other cancers. However, the mechanisms by which gastric cancer cells overcome an antitumor immune response are poorly understood.…”
Section: Introductionmentioning
confidence: 69%
“…Cell-mediated local antitumor immunity conferred by the TIL may play a pivotal role in controlling progression and/or metastasis (Vose and Moore 1985;Koyama et al 1992;Hoshino et al 1997). Furthermore, it has been reported that FasL expressed in tumor cells may be responsible for the elimination of TIL within tumor tissues in vivo (Hahne et al 1996;Strand et al 1996;Niehans et al 1997;Shiraki et al 1997;Bennett et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the FasR counterattack against immune eector lymphocytes, possibly bearing CD8 + CD11b ) , CD8 + CD28 + , and CD8 + S6F1 + phenotypes (Koyama et al 1992), allows maintaining the immune privileged status by metastatic carcinoma, but not by primary carcinoma of the stomach. These mechanisms of tumor immune privilege may help to explain the progressive cancer invasion and/or metastasis without rejection by the immune system, despite the expression of tumor rejection antigens and (Hoshino et al 1997;Suzuki et al 1999). In addition, the expanded eector TIL with high levels of FasR and FasL expression might kill either themselves or one another, because of the risk of autocrine suicide or paracrine fratricide (Nagata 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-rejection antigens in human gastric carcinoma, which are recognized by autologous cytotoxic T lymphocytes (CTL) have recently been identi®ed (Yasoshima et al 1995;Hoshino et al 1997). However, regardless of the demonstration of CTL against gastric carcinoma, metastatic carcinoma of the stomach especially is capable of progressive growth in patients, without rejection by the immune system.…”
Section: Discussionmentioning
confidence: 99%